DISHARMONISASI ANTARA MAHKAMAH KONSTITUSI DAN MAHKAMAH AGUNG DIHUBUNGKAN DENGAN ASAS KEPASTIAN HUKUM (Studi Putusan Nomor 30/PUU-XVI/2018 dan Putusan Nomor 65 P/HUM/2018 dengan Pemohon Oesman Sapta Odang) - Angghie Permatasari; Lusy Liany; Amir Mahmud (Institut Agama Islam Negeri Batusangkar, 2020)
Disharmonization between the Constitutional Court's Decision and the Supreme Court's Decision related to the case of the executive (functionary) of political parties in the nomination of DPD RI members in the 2019 General Election. The research method used was normative juridical research, using secondary data. The results of the discussion are: First, disharmony between the Constitutional Court Decision Number 30 / PUU-XVI / 2018 and the Supreme Court Decision Number 65 P / HUM 2018 in the nomination of DPD RI members in the 2019 General Election related to the phrase